Estimating the trajectory of a space vehicle passing by the Moon using Kalman Filter - Ferreira, A. F.S.; Kuga, H. K.; Prado, A. F.B.A.; Winter, O. C. [UNESP] (IOP Publishing, 2015)
The trajectory of a spacecraft going to the periapsis of its orbit around the smaller body of a binary system is estimated from the observed data using a Kalman Filter. Simulations of the trajectories will be made to generate the data of the spacecraft position. When observed from the Earth, using a fixed star as a reference, we have the spacecraft position as an angle function φ. This is the angle between spacecraft position vector and the star position vector. The result shows that Kalman Filter can be used successfully for trajectory estimation, if adequate accuracy is available for the angle observations.